Free Thyroxine Concentrations Moderate the Response to a Cognitive Remediation Therapy in People With Early Psychosis: A Pilot Randomized Clinical Trial - Estrada, Francesc; Crosas, Josep Maria; Ahuir, Maribel; Pérez-Muñoz, Sara; Zabala, Wanda; Aguayo, Raquel; Barbero, Juan David; Montalvo, Itziar; Tost, Meritxell; Llauradó, Laura; Guardia, Armand; Palao, Diego; et al. (Frontiers in Psychiatry, 2020)
INTRODUCTION: Cognitive deficits are a cause of functional disability in psychotic disorders. Cognitive remediation therapy (CRT) might be applied to improve these deficits. We conducted a pilot study to explore whether thyroid hormones might predict the response to CRT in patients with recent-onset psychosis (ROP). METHODS: Twenty-eight stable ROP outpatients (9 women) were randomized to receive computerized CRT (N=14) or treatment as usual (TAU) (N=14), over three months. Both cognitive and thyroid functions were assessed at the baseline and after those three months to all patients. A full cognitive battery (CANTAB) was administered before and after the treatment. Serum levels of thyroid-stimulating hormone (TSH) and free thyroxine (FT4) were measured. FT4 concentrations were recoded into a dichotomic variable (FT4 group) based on the median of the sample (1.2 ng/dL). Data were analyzed on an intention-to-treat basis with linear mixed models. Afterwards, we offered CRT to all participants from the TAU group and seven enrolled CRT, reassessing them when finished. Secondary analyses were repeated in a sample of 14 participants who completed the CRT (either from the beginning or after the TAU period) and attended at least one third of the sessions. RESULTS: The linear mixed models showed a significant time x CRT x FT4 group effect in two cognitive tasks dealing with executive functions and sustained attention (participants with higher FT4 concentrations worsened executive functions but improved sustained attention after CRT). In the secondary analysis including all patients assigned to CRT, higher FT4 concentrations were associated with a poorer response in verbal memory but a better response in spatial working memory. CONCLUSIONS: Free thyroxine concentrations moderate the response to a CRT in patients with early psychosis.